Routine laboratory surveillance of antimicrobial resistance in community-acquired urinary tract infections adequately informs prescribing policy in England. Issue 2 (27th May 2020) - Watts, Vicky; Brown, Benjamin; Ahmed, Maria; Charlett, André; Chew-Graham, Carolyn; Cleary, Paul; Decraene, Valerie; Dodgson, Kirsty; George, Ryan; Hopkins, Susan; Esmail, Aneez; Welfare, William
Abstract: Objectives: To assess whether resistance estimates obtained from sentinel surveillance for antimicrobial resistance (AMR) in community-acquired urinary tract infections (UTIs) differ from routinely collected laboratory community UTI data. Methods: All patients aged ≥18   years presenting to four sentinel general practices with a suspected UTI, from 13 November 2017 to 12 February 2018, were asked to provide urine specimens for culture and susceptibility. Specimens were processed at the local diagnostic laboratory. Antibiotic susceptibility testing was conducted using automated methods. We calculated the proportion of Escherichia coli isolates that were non-susceptible (according to contemporaneous EUCAST guidelines) to trimethoprim, nitrofurantoin, cefalexin, ciprofloxacin and amoxicillin/clavulanic acid, overall and by age group and sex, and compared this with routine estimates. Results: Sentinel practices submitted 740 eligible specimens. The specimen submission rate had increased by 28 specimens per 1000 population per year (95% CI 21–35). Uropathogens were isolated from 23% (169/740) of specimens; 67% were E. coli (113/169) . Non-susceptibility of E. coli to trimethoprim was 28.2% (95% CI 20.2–37.7) on sentinel surveillance (33.4%; 95% CI 29.5–37.6 on routine data) and to nitrofurantoin was 0.9% (95% CI 0–5.7) (1.5%; 95% CI 0.7–3.0 on routine data). Conclusions: Routine laboratory data resulted in a small overestimation in resistance (although the difference was not statistically significant) and our findings suggest that it provides an adequate estimate of non-susceptibility to key antimicrobials in community-acquired UTIs in England. This study does not support the need for ongoing local sentinel surveillance.